췌장의 파골세포양 거대세포 미분화 암종 1예 - 전영훈; Younghun Jeon; 소훈섭; Hoonsub So; 구자흥; Jaheung Koo; 나양원; Yang Won Nah; 임현수; Hyunsoo Lim; 김빛나리; Binnari Kim; et al. (Korean journal of pancreas and biliary tract, 2023)
파골세포양 거대세포형 미분화 암종은 췌장암의 1%만을 차지하는 흔치 않은 암종으로 알려져 있다. 저자들은 39세 남자에게서 진단된, 수술 및 항암치료를 시행한 1예를 소개하고자 한다. Undifferentiated pancreatic carcinoma with osteoclast-like giant cells (UC-OGC) is uncommon, accounting for only 1% of all pancreatic carcinomas. We report a case of a 39-year-old man with undifferentiated pancreatic carcinoma with osteoclast-like giant cells who underwent successful surgical resection and chemotherapy.